1979
DOI: 10.1080/00218467908544609
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies of the Strength of an Adhesive Joint in a State of Combined Stress

Abstract: The adhesive strength of a butt-type specimen of two cylinders is experimentally studied. Combined stresses are applied on the adhesive layer by subjecting the specimen to combined axial load, torsion and internal pressure. The effects of the surface roughness, the thickness of adhesive layers and the combined stresses on the adhesive strength are examined for the specimens of various metals bonded with epoxy resin. The adhesive failure locus under the combined stress state are represented by a polynomial equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…The same result that related to adhesive strength and adhesive thickness has been observed [5][6][7]. On the other hand, the study of the effects of surface roughness, adhesive thickness and combined stresses on the adhesive strength for various metals bonded with epoxy resin has been also discussed [8].…”
Section: Introductionsupporting
confidence: 58%
“…The same result that related to adhesive strength and adhesive thickness has been observed [5][6][7]. On the other hand, the study of the effects of surface roughness, adhesive thickness and combined stresses on the adhesive strength for various metals bonded with epoxy resin has been also discussed [8].…”
Section: Introductionsupporting
confidence: 58%
“…(16), the singular stress field around the notch tip is defined in terms of notch stress intensity factor K I, 1 λ , which is defined in Eq. (17). Fig.…”
Section: Usefulness Of Fictitious Crack Modelmentioning
confidence: 92%
“…It is known that the adhesive strength c σ increases with decreasing the adhesive thickness [2][3][4][5]. The previous studies suggested this is because more defects and cavities are included in the thick adhesive layer [17]. The experimental studies also suggested that the residual strain of adhesive layer may affect the results [18][19][20][21].…”
Section: Introductionmentioning
confidence: 96%